2022
DOI: 10.1049/mna2.12114
|View full text |Cite
|
Sign up to set email alerts
|

Metal enhanced fluorescence of different metallic nanoclusters deposited on silver dendritic nanostructures

Abstract: Plasmonic nanoclusters (NCs) have been introduced as new fluorescent materials that have low toxicity and do not undergo photo‐bleaching. Several factors including size and type of the NCs, surface chemistry and even solvent affect their luminescence. Despite extensive studies on tuning the fluorescence properties of NCs by manipulation of the above‐mentioned factors, very few researches have been focused on metal enhanced fluorescence (MEF) of them. In this study, the fabrication of silver dendritic nanostruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…MEF occurs when a fluorophore is situated in an amplified electromagnetic field produced by far-field excitation of plasmonic metal nanoparticles and surfaces. In addition to the signal amplification, other significant spectral alterations, such as shortened lifetime, improved photo-stability, and longer distances for resonance energy transfer (RET) of fluorescence, have been documented in MEF [19]. It has also been observed that shape and surface morphology of plasmonic NPs influences optical properties.…”
Section: Introductionmentioning
confidence: 99%
“…MEF occurs when a fluorophore is situated in an amplified electromagnetic field produced by far-field excitation of plasmonic metal nanoparticles and surfaces. In addition to the signal amplification, other significant spectral alterations, such as shortened lifetime, improved photo-stability, and longer distances for resonance energy transfer (RET) of fluorescence, have been documented in MEF [19]. It has also been observed that shape and surface morphology of plasmonic NPs influences optical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Nanosilver, as a new-style functional material owned characteristic physical and chemical properties, has gained great attention, which can be used for optical material [1], antibacterial [2], biosensor [3], battery electrode [4], and catalysis [5]. With environmental problems becoming more and more serious, nanosilver for catalysis has more and more been considered, but different morphologies have a very important impact on catalysis performance.…”
Section: Introductionmentioning
confidence: 99%
“…16 More importantly, the fluorescence properties of the complexes are easily affected by environmental factors such as temperature, metal ions, and solvent molecules. [17][18][19][20][21][22] Thus, they have great potential as fluorescent probes. To date, research on the detection of harmful gases using manganese (II) complexes is still limited, and hence, the detection and identification of chloroform is almost impossible.…”
mentioning
confidence: 99%